2023
DOI: 10.3389/fphys.2023.1205463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 24-week exercise program on anthropometric, body composition, metabolic status, cardiovascular response, and neuromuscular capacity, in individuals with intellectual and developmental disabilities

Abstract: Introduction: The prevalence of overweight and obesity has increased in the last decades, including in people with Intellectual and Developmental Disabilities (IDD). This is even more concerning when it is globally accepted that a low physical condition contributes to the deterioration of functionality and increases the risk of developing chronic diseases during life, with effective implications for health and well-being. The aim of the present study is to investigate the effects of two physical exercise inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Given this population’s tendency towards a sedentary lifestyle [ 7 ], which tends to negatively affect QoL [ 11 ], with lower levels of functional mobility, essential for carrying out daily life tasks [ 14 ], participation in programs of this nature seem to have positive and significant effects on the QoL and well-being of people with IDD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this population’s tendency towards a sedentary lifestyle [ 7 ], which tends to negatively affect QoL [ 11 ], with lower levels of functional mobility, essential for carrying out daily life tasks [ 14 ], participation in programs of this nature seem to have positive and significant effects on the QoL and well-being of people with IDD.…”
Section: Resultsmentioning
confidence: 99%
“…This population usually has a sedentary lifestyle [ 7 ], with low levels of physical activity (PA) [ 8 , 9 , 10 ], which tends to negatively affect their quality of life (QoL) [ 11 ]. Research has highlighted the positive impact of PA and physical exercise (PE) in preventing diseases such as type II diabetes, hypertension and obesity [ 7 , 12 ], as well as their contribution to improving physical fitness, with benefits for the individual’s general state of health, QoL and average life expectancy [ 13 , 14 ]. In this sense, different studies have shown that the practice of PA [ 7 , 15 ], PE [ 6 , 16 ] and sport [ 17 , 18 ] seems to be associated with an improvement in the perception of well-being and QoL of adults with IDD.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Ferreira et al [ 75 ], two programs are presented that have been adapted, one of which uses low-cost materials. These programs have already been shown to be effective and to have an acceptable adherence rate [ 76 ]. Tomé et al [ 77 ] also presents an intervention program using play, games, and pre-sport modalities, increasing enjoyment and the motivation to practice.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study by Jacinto et al [136] evaluated the effects of two 24-week exercise programs on indices of health and fitness in institutionalized individuals with intellectual and developmental disabilities. Study findings revealed significant differences in cardiovascular response, with significant changes in HR observed at midterm assessments, while SBP and DBP variables did not show significant differences between groups.…”
Section: Discussionmentioning
confidence: 99%